2004
DOI: 10.5713/ajas.2004.947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding High and Low Energy Levels during Late Pregnancy on Performance of Crossbred Dairy Cows and Their Calves

Abstract: The present research was designed to evaluate the effects of pre and post-partum energy level and feeding pattern on the performance of crossbred dairy cows and their calves under farm conditions. A total of 16 crossbred dairy cows were divided into two equal groups on the basis of their body weight and milk production. One group was given 30% less and the another was given 30% more energy than MAFF's (1984) recommendation. After calving all cows were given same ad.libitum diet to assess the effects of feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…This might be due to pregnancy stress and body tissues loss through milk production during postpartum period. This statement is supported by Khan et al (2004) who reported that BCS of the postpartum cow didn't improve after allowing concentrate supplementation during late pregnancy. However, Kokkonen et al (2004) found improved BCS of dairy cows by supplying a higher amount (4.7 kg/h/d) of concentrate at prepartum period.…”
Section: Dry Matter Intake and Growth Performancementioning
confidence: 75%
“…This might be due to pregnancy stress and body tissues loss through milk production during postpartum period. This statement is supported by Khan et al (2004) who reported that BCS of the postpartum cow didn't improve after allowing concentrate supplementation during late pregnancy. However, Kokkonen et al (2004) found improved BCS of dairy cows by supplying a higher amount (4.7 kg/h/d) of concentrate at prepartum period.…”
Section: Dry Matter Intake and Growth Performancementioning
confidence: 75%
“…These results are in agreement with those obtained by Hung et al (1993), Youssef et al (1998), El-Gaafarawy et al (2003) and El-Ashry et al (2003) who found that birth weight of calves didn't reflected by the level of nutrition, but rather maternal body weight during pregnancy. Khan et al (2004) found that birth weight of calves in the low-energy group was lower (P<0.05) than that of calves in the high-energy group. Cows that were Means in the same row with different letter differ significantly (P < 0.05).…”
Section: Reproductive Parametersmentioning
confidence: 79%
“…This method grades the cow's conditioning status on a six-point scale (1)(2)(3)(4)(5)(6), where 1 reflects very thin and 6 reflects very fat animal. Cows' body condition was scored on the day of their inclusion in the experiment and after 30 days interval till the end of the experiment.…”
Section: Body Condition Score (Bcs)mentioning
confidence: 99%
“…The influence of maternal nutrition on the early growth performance of offspring's is mainly mediated through its influence on the birth weight besides milk yield and quality. Although there are many studies that have demonstrated a positive impact of maternal nutrition on the birth weight of calves [2][3][4], its effects on the early growth performance of the calves is often without agreement. There are positive reports of the effect of maternal plane of nutrition on growth performance of calves.…”
mentioning
confidence: 99%